Training on making biopesticides as effort to strengthen organic agriculture by Taruna Tani Lestari - Arthaka Damascena; Divanissa Kusumaningrum; Emi Widiyanti; Ines Fitriana; Lintang Mukti; Perdana Mangayu Bagyo; Rival Fairuz; Salsyabila Fajrin; Samuel Suryowidhi (University of Merdeka Malang, 2023)
Pests are one of the problems in agriculture. The use of organic pesticides still needs to be developed in Gentungan Village. Training in making biopesticides is useful for controlling pests and diseases using environmentally friendly natural ingredients. In addition, to foster the ability of Taruna Tani Lestari in Gentungan Village to make biopesticides independently and disseminate them to local farmers. The implementation method involved presentations, questions and answers, practices, modules, and evaluation designs. The material presented included the meaning and benefits of biopesticides, the natural ingredients used, the correct dosage, and the stages of making biopesticides. After the training, the output obtained included members of Taruna Tani Lestari knowing the natural ingredients for making biopesticides, members of Taruna Tani Lestari understanding the benefits of using biopesticides, members of Taruna Tani Lestari being able to make biopesticides independently and educate local farmers and display biopesticide products.